A Study of Effectiveness of Remedial Reading Programme for Slow Learners: Addressing the Needs of Slow Learners through a Coordinated Remedial Reading Programme (Journal of Advances and Scholarly Researches in Allied Education, 2015)
A compelling Remedial reading program is one that is coordinated by a profoundly prepared therapeutic teacher and has picked up the collaboration what's more, support of educators, heads, and guardians. The viable of such a program is accomplished just by long range arranging in which everybody included is made aware of the points and destinations of the program. A Remedial reading program is produced when a requirement for it exists. Educators may encounter a requirement for an extraordinary perusing program because of meeting with disappointment in training certain understudies by ordinary techniques. Chairmen may feel a requirement for a Remedial reading program in the wake of concentrate complete plans to move forward classroom direction in perusing. Experiencing the requests of a technological age, people in general may express a want for such a program. By and by, once the need is built up, the great educational system makes quick move